Dissociations between coaches` fatigue rating, athletes` perceived fatigue, and objective training load - Kósa, L.; Körmendi, J.; Ihász, F.; Köteles, F. (International Journal of Sports Science & Coaching, 2023)
Players` fatigue after practice is an important indicator of the actual training status for the coach. However, fatigue is not a unitary construct; it has objective (physiological) and perceived (experiential) aspects, which are not necessarily strongly related. The present study aimed to assess the association between coaches` and athletes` perception of fatigue and objectively assessed training load (TL). Participants were 61 elite players of five sport teams of two sports (basketball and football) and their coaches. Players` and coaches` perception of fatigue and objective data on TL provided by the Polar Team Pro system was obtained for 276 practice sessions overall. The association between coaches` and athletes` fatigue rating was .43 (p < .001), between coaches` fatigue rating and TL was .5 (p < .001), and between athletes` fatigue rating and TL was .45 (p < .001). Linear regression with TL as the criterion variable and coaches` and athletes` fatigue rating as predictor variables explained 32.8% of the total variance. As the discordance between coaches` estimation of fatigue, athletes` perceived fatigue, and objective TL appears substantial, coaches should always take into consideration the latter two indicators. Future research with a translational focus is needed to help coaches to find an optimal balance among various indicators of fatigue in the determination of the load for the subsequent training sessions.